Evaluation of Natural Radioactivity Levels and Transfer Factor of Soil and Plant, Siwa Oasis, Egypt - Begawy, Hekmat El; H, Salama M; Ali, H (International Journal of Environmental Sciences, 2019)
Purpose: The study sought to evaluate natural radioactivity levels and transfer factor of soil and plant, Siwa Oasis in Egypt. Methodology: In this work, 23 plant samples and 23 soil samples were collected directly from the central and western parts of Siwa oasis for radioactivity analysis. Global Positioning System device (eTrex, Personal Navigator, Garmin Ltd) was used to define the latitudes and longitudes of sampling points. Each plant sample was dried, grind into fine powder and weighed. The activity concentrations of 238U (226Ra) series and 232Th series and 40K in water samples were measured at Egyptian Nuclear and Radiological Regularity Authority (ENRRA). Results: For plant samples, the maximum activity values of 226Ra (238U) series and 232Th were 35 Bq/kg and 27 Bq/kg, respectively. Most values of activity concentrations of 226Ra (238U) series and 232Th series were under the detection limits (0.7 and 0.6) Bq/kg, respectively. For 40K the activity concentration ranges from 338 to 2102 Bq/kg in the plant samples. For soil samples, the activity concentrations were ranges from <0.7 to 104 Bq/kg, from < 0.6 to 67 Bq/kg, and from 82 to 1969 Bq/kg for 226Ra (238U) series, 232Th series, and 40K, respectively. The total absorbed dose rate in air ranged from 10 to 171nGy/h. The external hazard index was ranged from 0.07 to 0.95, and the annual effective dose ranged from 0.01 to 0.06. The highest value of transfer factors in case of uranium and thorium were 1.41 and 0.40, respectively. While for 40K the highest value of transfer factor was 36.4 and the mean value was equal 7.19. Unique contribution to theory, practice and policy: Since plant uptake from soil was probably influenced by various factors such as soil characteristics, amount and physico-chemical form of radionuclides in soil, plant species, temperature, rainfall, and agricultural management, these parameters should be further investigated in the future. The results obtained from this study can be considered as baseline data for TFs of natural radionuclides from soil to plants and also serve as a guideline for future monitoring and assessment of naturally occurring radioactive material in Siwa Oasis.